The importance of chosen attributes of a digital postal service in shaping its quality in the opinion of customers at the age of 18-30 - Kamila Kowalik (Kazimierz Wielki University, 2020)
The purpose of the article is to present the importance of the chosen digital postal service's attributes in shaping its quality in the opinion of young customers at the age of 18-30. The first part contains the theoretical framework of service quality, digital services, postal market and digital competences. Afterwards, the results of anonymous survey have been presented. The study has been conducted among fifty respondents at the indicated age and  it consisted of assessing the meaning of nine chosen quality factors on a Likert scale of 1-5. The results contributed to the formulations of conclusions on the validity of chosen determinants of the digital postal service quality for customers at the age of 18-30.